2016
DOI: 10.7554/elife.20085
|View full text |Cite
|
Sign up to set email alerts
|

A plasma membrane template for macropinocytic cups

Abstract: Macropinocytosis is a fundamental mechanism that allows cells to take up extracellular liquid into large vesicles. It critically depends on the formation of a ring of protrusive actin beneath the plasma membrane, which develops into the macropinocytic cup. We show that macropinocytic cups in Dictyostelium are organised around coincident intense patches of PIP3, active Ras and active Rac. These signalling patches are invariably associated with a ring of active SCAR/WAVE at their periphery, as are all examined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
253
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(286 citation statements)
references
References 84 publications
23
253
2
Order By: Relevance
“…Thirdly, macropinocytic cups are not necessarily formed de novo each time. Recent analysis of macropinosome dynamics in Dictyostelium found that cups were frequently produced by the splitting of pre‐existing ones . Similar behaviour has been described for pseudopods, which spontaneously self‐assemble and proliferate by splitting in both amoebae and immune cells .…”
Section: How Do You Construct a Macropinocytic Cup?mentioning
confidence: 57%
See 3 more Smart Citations
“…Thirdly, macropinocytic cups are not necessarily formed de novo each time. Recent analysis of macropinosome dynamics in Dictyostelium found that cups were frequently produced by the splitting of pre‐existing ones . Similar behaviour has been described for pseudopods, which spontaneously self‐assemble and proliferate by splitting in both amoebae and immune cells .…”
Section: How Do You Construct a Macropinocytic Cup?mentioning
confidence: 57%
“…The Ras family of small GTPases are also important in macropinocytosis. Expression or injection of constitutively activated (oncogenic) Ras is sufficient to induce ruffling and macropinocytosis in fibroblasts and active Ras localises to macropinocytic cups in both macrophages and Dictyostelium . Ras functionally sits between growth factor receptors and activation of class I PI‐3 kinases via their Ras‐binding domains, providing a direct mechanism for stimulated macropinocytosis .…”
Section: Temporal Signals During Cup Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The expanding cup-like protrusions seen in lattice light sheet microscopy (Chen et al, 2014) of randomly migrating vegetative Dictyostelium cells could be explained by propagating STEN waves driving cytoskeletal activity. Consistently, actin binding proteins rim the cup-like structure which is filled with a broader zone of Ras and PI3K activity (Veltman et al, 2016; Pollitt et al, 2006). These structures, referred to as macropinosomes, are abundant in axenic cells which have been selected for fluid uptake (Maniak, 2001).…”
Section: Propagating Sten Waves and The Protrusions That Underlie Motmentioning
confidence: 85%